The Social and Cultural Determiners of Patterns of Mate Selection (the Study of Married Women 15 to 35 Years, Lamerd City, Fars Province) - mansour tabiee; marzieh shamsipour (توسعه اجتماعی, 2019)
In the past few decades, marriage patterns have been changing in Iran that is necessary to understand the affecting factors on these changes. The aim of this study is to investigate the social and cultural factors on patterns of marriage. Marriage patterns examined in this study are how to choose a mate and mate selection criteria. The methodology of this research is field observation. The tool used to collect data is researcher made questionnaire. The theoretical framework is based on the theory of evolution culture and values by Inglehart. The population of this research are married women in Lamerd city with the overall sample of 390 people. The findings show that social and cultural variables  had influence on both of married women surveyed (how to choose a mate and mate selection criteria) and among variables, only the variable of location had influenced on how to choose a spouse and location and education have been effective on female mate selection criteria. The results also showed that social factors such as family income, parental care and the importance of friendship and cultural variables such as religious beliefs have been effective on how to choose husbands. The results showed that the variables of education, place of residence, parental care, social class, religious beliefs, physical and metaphysical values have a significant effect on female mate selection criteria but four other variables including age, education, parents income and the importance of friends don’t have a significant impact on women marriage standards. The overall results of the study show that contextual, social and cultural factors influence on marriage patterns.